Kinematics During Lower Extremity Functional Screening Tests – Are They Reliable and Related to Jogging? - Whatman, C; Hing, W; Hume, P (Elsevier, 2011)
Purpose To investigate the within-day and between-day reliability of 3D lower extremity kinematics during five lower extremity functional screening tests and to assess the association between these kinematics and those recorded during jogging. Methods Peak three-dimensional lower extremity kinematics were quantified in 25 uninjured participants during five lower extremity functional tests and jogging. A nine camera motion analysis system (Qualysis Medical AB, Sweden) was used to capture three trials of all tests. All functional tests were repeated by 10 participants one to two days later. Visual 3D (C-Motion Inc, USA) and Labview were used to process all data. Intraclass correlation coefficients (ICC) and typical errors (TE) were used to assess within- and between-day reliability of all variables. Pearson correlation coefficients were used to evaluate the association between peak joint kinematics during the functional tests and jogging. Results For the majority of kinematic variables the within-day reliability was excellent (ICC ≥ 0.92) and the between-day reliability was excellent to good (ICC ≥ 0.80). The correlation between kinematics of the functional tests and jogging was generally large to very large (r = 0.53 to 0.93). Conclusions These results suggest these lower extremity functional screening tests should prove a useful clinical tool when assessing dynamic lower extremity alignment.
Keywords: Reliability; Kinematics; Lower extremity; Functional tests